Pengaruh Pembelajaran Responsi Pada Mata Kuliah Aljabar Linier Terhadap Hasil Belajar Mahasiswa Program Studi Pendidikan Matematika FIP UPH - Kurnia Putri S. Dirgantoro; Melda Jaya Saragih; Tanti Listiani (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2017)
Linear Algebra is a mathematics subject needed to be mastered well by mathematics education students. Mathematics student-teachers need to master it well as it is one of the basic of mathematics school. However, students’ achievement as the learning outcomes of understanding Linear Algebra is not maximized well due to limitations in exploring and elaborating the concepts in it. Therefore, the response/tutorial program is regarded as one of the solutions that can be used to maximize student understanding. Through the response/tutorial program, students can explore concepts and issues related more depth. Thus, this study aims to look at the effect on the response/tutorial program of students’ achievement in learning Linear Algebra of FIP UPH Mathematics Education. The findings showed that there is a significant effect on the application of response/tutorial program toward the learning outcomes of students of Mathematics Education at FIP UPH. Keywords: tutorial program, student’s achievement